Microchannel Fabrication on Glass Materials for Microfluidic Devices - Hwang, Jihong; Cho, Young Hak; Park, Min Soo; Kim, Bo Hyun (International journal of precision engineering and manufacturing, 2019)
Microchannels are the main features that characterize microfluidic devices. Also, glass is given priority in selecting a substrate material in the development of microfluidic devices due to its high degree of transparency, high chemical resistance, inertness to most substances, ability to sustain higher temperature, biological compatibility, and relatively low non-specific adsorption. However, the high cost and time-consuming labor for fabricating microchannels on glass limit the development of glass-based microfluidic devices, especially for point-of-care test devices. Therefore, it is important to have a capability for fabricating microchannels on glass more efficiently. In this context, the present paper reviews the processes applicable for fabricating microchannels on glass, which include chemical, mechanical, laser-based, and other processes. The state of the art for these processes, and their advantages and limits are also addressed, which will guide in selecting the processes suitable for constructing glass-based microfluidic devices.